Validação de técnica hemostática do complexo arteriovenoso ovariano na ovariosalpingohisterectomia de gatas - Silveira, Camila Pinho Balthazar da [UNESP]; Araújo, Marília Silva Carneiro; Horr, Mônica [UNESP]; Alencar, Elane Arrais Machado; Rigaud, Roberta [UNESP]; Oriá, Arianne Pontes; Martins Filho, Emanoel Ferreira [UNESP]; Costa Neto, João Moreira (Universidade Federal de Goiás, 2015)
The present study aimed at describing ovarian arterial venous complex (OVAC) obliteration technique consisting in tying a knot over its own axis. It also aimed at evaluating the efficacy of this hemostatic technique in queens ovariosalpingohisterectomy, as well as checking partial OVAC obliteration time and total procedure time. After previous training – based on alternative methods – for the demanded surgical skills acquisition, in vivo surgical procedures were conducted. Once gathered the necessary skills, an experimental study was carried in order to compare this technique with the linking technique in which three hemostatic clamps are used. In vivo training, firstly applied in healthy queens, and later in uterine affection carriers, helped consolidating the dexterity previously acquired through alternative practice methods, and also contributed to the feasibility verification of the described technique, which showed to be effective. Comparative study did not reveal any significant statistic difference between both groups on total surgical elapsed time (p =0.2848) and time spent for the right OVAC obliteration (p=0.1036), however significant difference was observed on the left OVAC obliteration (p=0.0001). The results obtained during trans-operatory observation led to the conclusion that the described technique is feasible and provides appropriate OVAC hemostasis.

O estudo objetivou descrever a técnica de obliteração do complexo arteriovenoso ovariano (CAVO) por meio da confecção de um nó sob seu próprio eixo, além de avaliar a eficácia desta técnica hemostática na ovariosalpingohisterectomia de gatas, bem como averiguar os tempos parciais de obliteração dos CAVOs e o tempo total do procedimento. Após treinamento prévio, com auxílio de métodos alternativos para ganho de habilidade cirúrgica, foram realizados procedimentos cirúrgicos in vivo. Realizou-se estudo experimental com finalidade de comparar a técnica proposta com a técnica de ligadura com três pinças hemostáticas. O treinamento in vivo, inicialmente em gatas hígidas e, posteriormente, em portadoras de afecções uterinas, serviu para consolidar a destreza adquirida por meio de métodos alternativos e para averiguar a exequibilidade da técnica descrita, que se mostrou eficaz. No estudo comparativo não houve diferença estatística significativa entre o tempo cirúrgico (p=0,2848) e a obliteração do CAVO direito (p=0,1036) entre os dois grupos, porém foram observadas diferenças significativas no tempo de obliteração do CAVO esquerdo (p=0,0001). Diante dos resultados obtidos a partir das avaliações realizadas no período de observação transoperatória, podemos inferir que a técnica descrita é exequível e promove adequada hemostasia do CAVO.
Hemostasis technique validation of ovarian arterial venous complex in queens ovariosalpingohisterectomy
Keywords: Feline; Surgery; Vascular obliteration; Cirurgia; Felino; Obliteração vascular